2013
DOI: 10.1074/jbc.m112.413310
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Per Arnt Sim (PAS) Domain Protein 4 (NPAS4) Regulates Neurite Outgrowth and Phosphorylation of Synapsin I

Abstract: Background: NPAS4 is involved in memory formation, but its roles in neuronal function remain to be fully elucidated. Results: NPAS4 increased CDK5-dependent phosphorylation of synapsin I that was associated with neurite elongation. Conclusion: NPAS4 induced CDK5-dependent phosphorylation of synapsin I to facilitate neurite outgrowth. Significance: NPAS4 plays an important role in the structural and functional plasticity of neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 48 publications
(57 reference statements)
1
25
0
Order By: Relevance
“…Neuronal PAS domain protein 4 (Npas4) is a transcription factor encoded by a neuronal activity-dependent immediate-early gene and is required for activity-dependent inhibitory synapse development, activity-dependent changes in inhibitory synaptic connectivity, and neurite outgrowth [62][63][64]. Npas4 knockdown selectively reduces the number of inhibitory synapses formed on both the soma and dendrites, suggesting that Npas4 may regulate the development of inhibitory synapses originating from multiple interneurons [62].…”
Section: Schemaɵcs Of Inhibitory Synapse Organizersmentioning
confidence: 99%
“…Neuronal PAS domain protein 4 (Npas4) is a transcription factor encoded by a neuronal activity-dependent immediate-early gene and is required for activity-dependent inhibitory synapse development, activity-dependent changes in inhibitory synaptic connectivity, and neurite outgrowth [62][63][64]. Npas4 knockdown selectively reduces the number of inhibitory synapses formed on both the soma and dendrites, suggesting that Npas4 may regulate the development of inhibitory synapses originating from multiple interneurons [62].…”
Section: Schemaɵcs Of Inhibitory Synapse Organizersmentioning
confidence: 99%
“…To test this hypothesis, we conducted in vitro experiments to examine whether 5-HT 2A receptor expressed in cultured neuronal cells was internalized in response to FSS. Based on our simulation mentioned above, we applied pulsatile FSS with an average magnitude of 0.91 Pa to Neuro2A cells, which exhibit neuronal phenotypes and morphology (Goshima et al, 1993;Yun et al, 2013), using a system we previously reported (Yoshino et al, 2013). Similar to what was observed after 5-HT administration, FSS application (0.91 Pa, 0.5 Hz, 30 min) caused internalization of 5-HT 2A receptors expressed in Neuro2A cells ( Figure 3A).…”
Section: Fss On Neuronal Cells Induces 5-ht 2a Receptor Internalizationmentioning
confidence: 67%
“…The neuronal per arnt sim domain protein 4 (NPAS4) mRNA expression was decreased in the female rat barrel cortex under conditions of input‐deprivation. NPAS4 has been implicated in the development of inhibitory synapses as well as neurite outgrowth (Lin et al, ; Yun et al, ). There is a direct relationship between neuronal activity and NPAS4 expression, which is mediated through intracellular calcium.…”
Section: Discussionmentioning
confidence: 99%